Not all foreign direct investment is foreign: the extent of round-tripping - Maria Borga (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Some foreign investment represents domestic funds that have been sent abroad before returning to the domestic economy, called round-tripping. Traditional FDI statistics do not distinguish round-tripping from genuine foreign investment. This Perspective argues for countries to produce statistics by ultimate investing country to identify the round-tripping in their economies.
Keywords: 330